An Early Prosthetic Valve Endocarditis in Presence of COVID-19-Associated Pneumonia - Popov, Volodymyr V.; Bolshak, Oleksandr O.; Boukarim, Valery Zh.; Khoroshkovata, Olena V.; Trembovetska, Olena M. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. Coronavirus disease (COVID-19)-associated pneumonia was a dangerous disease at the beginning of 2021. However, there are almost no records of early infectious endocarditis of prosthetic heart valve in the presence of such a disease. We present an interesting clinical case of successful treatment of complicated pathology. The COVID-19 outbreak involved unique clinical complications that were superimposed on the progressive heart failure due to prosthetic mitral valve dysfunction (its detachment) which did not allow time for active antiinflammatory therapy. Urgent replacement of the prosthesis made it possible to eliminate the infection and paved the way for successful long-term antibacterial, antifungal and antiviral therapy. The aim. To determine the features of management of patients with complex clinical pathology: prosthetic valve endocarditis associated with COVID-19 and severe lung inflammation in the early postoperative period. Case report. This work presents rare clinical case. A 46-year old male patient underwent successful surgery (mitral valve replacement with posterior leaflet preservation and left atrium resection) at the Department of Surgical Treatment of Acquired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery and was discharged in satisfactory condition. One month later, he was hospitalized again and diagnosed with an early infectious endocarditis of prosthetic mitral valve and bilateral polysegmental COVID-19-associated pneumonia. After a week of medicinal preparation (antibacterial therapy), the patient underwent repeat mitral valve replacement in the presence of progressive heart insufficiency due to increasing paravalvular insufficiency. Postoperative period elapsed without significant complications. The patient was discharged in satisfactory condition on day 15 after surgery and primary rehabilitation. Conclusion. Having a specific etiology, pneumonia significantly damaged mitral prosthesis structures by increasing paravalvular insufficiency. Consequently, the patient underwent life-saving repeat mitral valve replacement in the presence of COVID-19-associated pneumonia and under massive antibacterial treatment which continued for 60 days after the patient’s discharge. An important element of successful treatment of COVID-19-associated pneumonia is the selection of adequate antibacterial, antifungal and antiviral drugs.